Fish cells persistently infected with nervous necrosis virus produce a small-molecule substance for reducing cellular metabolism and suppressing viral multiplication - Han Sol Lee; Toyohiko Nishizawa (Scientific Reports)
Abstract Nervous necrosis virus (NNV) of the genus Betanodavirus is one of the simplest RNA viruses pathogenic to a wide range of fish species. We established the SeGF, SeGE-22 and SeGB cell lines persistently infected with NNV (PI-SeGFNNV, PI-SeGE-22NNV and PI-SeGBNNV cells) by repeatedly subculturing the cells that survived NNV infection. The PI-SeGFNNV and PI-SeGE-22NNV cells continued to stably yield NNV in culture fluids at 106 to 107 median tissue culture infectious dose (TCID50)/ml even after 30–50 subcultures. The PI-SeGBNNV cells initially yielded NNV at 103.9 TCID50/ml but stopped yielding NNV after several passages. No significant morphological differences were observed between the naïve and PI-cells in either cell line. Antiviral activity suppressing the multiplication of NNV was detected in the culture fluids of all PI-cell lines. It significantly suppressed the growth (metabolism) of each cell line but did not directly influence NNV infectivity. However, this antiviral substance was not an interferon but a heat-stable (100 ºC for 3 min), small molecule with M r < 1000. When the PI-SeGBNNV cells stopped yielding NNV after subculturing several times, the production of the antiviral substance also ceased, indicating that the production of antiviral substance is initiated by NNV infection.